THE ROLE AND SIGNIFICANCE OF ART IN THE PSYCHE OF MILITARY PERSONNEL (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
this study explores the profound impact of art on the psychological well-being of military personnel, emphasizing how various artistic expressions such as visual arts, music, and theater can mitigate symptoms of post-traumatic stress disorder (PTSD), anxiety, and depression prevalent among service members. Drawing from recent empirical evidence between 2021 and 2025, the research highlights art's role in fostering emotional regulation, enhancing resilience, and promoting social integration, thereby underscoring its therapeutic value in military mental health programs. Ultimately, the findings advocate for the integration of art-based interventions into standard military psychological support systems to improve overall mentality and operational effectiveness.